Stavebně technologická etapa montáže průmyslové haly - Jekielek, Marek (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Bakalářská práce se zabývá stavebně technologickým projektem pro etapu montáže prefabrikovaného skeletu. Obsahuje technologický předpis pro montáž skeletu, projekt zařízení staveniště pro etapu montáže, časový plán montáže skeletu, finanční plán montáže skeletu, kontrolní a zkušební plán montáže, plán rizik hrozících při dané etapě a návrh strojní sestavy.

The objective of this thesis is the technological project of the construction phase of mounting prefabricated frame. Includes technological standard for mounting frame, the project construction site for the phase of mounting , the schedule of the phase of mounting frame, financial plan of the phase of mounting frame, controlling plan and test plan of the phase of mounting frame, the plan of risks at the phase of mounting frame, and mechanical assemblies plan.
Technological stage of realization mounting frame of factory building
Keywords: technologický předpis; časový plán; plán rizik; kontrolní a zkušební plán; zařízení staveniště; prefabrikát; montáž; strojní sestava; zvedací mechanismus; vázací prostředek; přepravní úchyt; technological standard; schedule; plan of risks; plan of inspections and tests; construction site; prefabricated part; mounting; mechanical assemblies; lifting mechanism; binding element; lifting system